Memorial Parking Trees: Resilient Modular Design with Nature-Based Solutions in Vulnerable Urban Areas - Fortino Acosta; Stephen Haroon (Land, 2021)
Nature-based solutions (NbS) include all the landscape’s ecological components that have a function in the natural or urban ecosystem. Memorial Parking Trees (MPTs) are a new variant of a nature-based solution composed of a bioswale and a street tree allocated in the road, occupying a space that is sub-utilised by parked cars. This infill green practice can maximise the use of street trees in secondary streets and have multiple benefits in our communities. Using GIS mapping and methodology can support implementation in vulnerable neighbourhoods. In this research, we based vulnerability assessments for London, Rio de Janeiro, and Los Angeles on the following three indicators: extreme temperature, air quality, and flood-prone areas. Evidence is emerging that disadvantaged populations may live at higher risks of exposure to environmental hazards. The income and healthcare accessibility of neighbourhoods are the two indicators that will help us target these communities for a better and faster decision-making process. The contrast between the results and the 15-min city concept supports our detecting and prioritising neighbourhoods for MPTS implementation, among other NbS solutions integrated into a more inclusive and sustainable urban design.